Analysis of Waves in the Oman Sea Using Numerical Software and Field Data - Homayun Kalantari; Kamran Lari; Afshin Mohseni Arasteh; Masoud Torabi Azad (Nīvār)
Accurate prediction of wave parameters is of great significance for marine and coastal operations. The very aim of the present research was to predict the wave characteristics for the northern coastal areas of the Sea of Oman using the MIKE 21 SW model. In this study, firstly, the generation of waves by wind with a spatial resolution of 0.1 degrees, a temporal resolution of 1 hr, and a suitable boundary condition was presented from the study data of the coasts of Iran (phase six - Makran beaches) with a temporal resolution of 1 hr. The results were validated with measurement data obtained from certain stations in 2016. Simulated wave parameters after calibration and adjustment of white capping coefficients as a wave loss parameter corresponded with the results of the measurement data at three stations with a strong correlation of 90%, 86% and 80% and an improvement value of 7.6%, 4 6.6%, and 27.18%, respectively. Moreover, the correlation coefficient of Tp and MWD in the Pasabandar station was 0.33 and 0.58, respectively. The results of this study also revealed that the dispersion index for three stations after calibration was 0.232, 0.363, and 0.684 for Hs, 0.338, 0.337, and 0.393 for Tp, and 0.149, 0.182, and 0.300 for MWD. By inferring from the simulation results and non-dimensional parameters of wave age and steepness, it can be concluded that the sea state and the wave climate are influenced by the waves caused by the northwest wind, monsoon, and the waves of the Indian Ocean. Wave steepness varied from 0.005 to 0.055 in different seasons such that discontinuity could be seen in the combined distribution of inverse wave age-wave steepness data in steepness of less than 0.01.